Strain Sensors: A Highly Skin‐Conformal and Biodegradable Graphene‐Based Strain Sensor (Small Methods 10/2018). Issue 10 (9th October 2018) - Wan, Shu; Zhu, Zhihong; Yin, Kuibo; Su, Shi; Bi, Hengchang; Xu, Tao; Zhang, Hongtao; Shi, Zhihui; He, Longbing; Sun, Litao
Abstract : In article number1700374, Litao Sun and co‐workers report a novel method to fabricate a strain sensor with ultrahigh skin conformity. The ultrahigh skin conformity, together with high sensitivity and rapid response time, makes the sensor attractive for precisely monitoring vital human signals and for integration in appliances with increased human‐machine interaction. Furthermore, this sensor is biodegradable, which is environment‐friendly.